2003
DOI: 10.1104/pp.103.025213
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Leachianone G 2″ -Dimethylallyltransferase, a Novel Prenyl Side-Chain Elongation Enzyme for the Formation of the Lavandulyl Group of Sophoraflavanone G in Sophora flavescens Ait. Cell Suspension Cultures

Abstract: Leachianone G (LG) 2ЈЈ-dimethylallyltransferase, a novel prenyl side-chain elongation enzyme, was identified in Sophora flavescens Ait. cultured cells. The enzyme transfers a dimethylallyl group to the 2ЈЈ position of another dimethylallyl group attached at position 8 of LG to form sophoraflavanone G, a branched monoterpenoid-conjugated flavanone characteristic to this plant. This membrane-bound dimethylallyltransferase required Mg 2ϩ (optimum concentration was 10 mm) for the reaction and had an optimum pH of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Following transient expression, the fluorescence of SfN8DT1-GFP was localized to dotted organelles in both cell types, whose size and pattern were highly similar to that of isoprene synthase, a typical plastid protein, used as a positive control (Sasaki et al, 2005). These results suggested that SfN8DT-1 was localized to plastids as the native enzyme in S. flavescens (Zhao et al, 2003) as well as prenyltransferase of other plant species (Dhillon and Brown, 1976;Biggs et al, 1990;Fellermeier et al, 2001). …”
Section: Subcellular Localization Of Sfn8dt-1mentioning
confidence: 51%
See 2 more Smart Citations
“…Following transient expression, the fluorescence of SfN8DT1-GFP was localized to dotted organelles in both cell types, whose size and pattern were highly similar to that of isoprene synthase, a typical plastid protein, used as a positive control (Sasaki et al, 2005). These results suggested that SfN8DT-1 was localized to plastids as the native enzyme in S. flavescens (Zhao et al, 2003) as well as prenyltransferase of other plant species (Dhillon and Brown, 1976;Biggs et al, 1990;Fellermeier et al, 2001). …”
Section: Subcellular Localization Of Sfn8dt-1mentioning
confidence: 51%
“…1). This intermediate, 8-dimethylallyl naringenin (8DN), is further hydroxylated to form leachianone G (LG) by 8DN 2#-hydroxylase (Yamamoto et al, 2001), and the second prenylation takes place at the prenyl side chain of LG catalyzed by LG 2$-dimethylallyltransferase (Zhao et al, 2003). Both prenylation reactions are Mg 21 dependent, plastid localized, and involve membranebound proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in cells fed 0.3 mM (2RS)-naringenin notable accumulation of two intermediates 8PN and LG was observed, although the content of SFG was almost the same as that in cells fed 0.1 mM (2RS)-naringenin-fed cells. These results suggest that the second prenylation step catalyzed by leachianone G 2Љ-dimethylallyltransferase (Zhao et al 2003a) is one of the regulatory steps in SFG biosynthesis. The amount of TM, derived from 5-deoxyflavanone liquiritigenin but not from 5-hydroxylated naringenin, decreased by the addition of (2RS)-naringenin.…”
Section: Prenylation Of (2s)-naringeninmentioning
confidence: 80%
“…That is, naringenin was first dimethylallylated to afford 8-prenylnaringenin (8PN) by plastid-located naringenin 8-dimethylallyltransferase, a stereospecific enzyme for (Ϫ)-(2S)-naringenin (Yamamoto et al 2000), then hydroxylated to leachianone G (LG) by endoplasmic reticulum-associated cytochrome P450 mono-oxygenase, 8-prenylnaringenin 2Ј-hydroxylase (Yamamoto et al 2001a). Finally, another dimethylallyl moiety was transferred to the 2Љ position of LG by leachianone G 2Љ-dimethylallyltransferase exist in the plastid to form SFG (Zhao et al 2003a).…”
mentioning
confidence: 99%